The Dilemma of Child Labor in South Kalimantan: Between Economic Necessity and the Right to Education - Sholihin, Rahmat; Jahra, Pati Matu; Salsabila, Saila (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2021)
This study examines the phenomenon of child labor in South Kalimantan, focusing on the underlying economic and social factors that drive children into the workforce. The research employs a qualitative approach, utilizing interviews and field observations in Banjarmasin and Martapura. Findings indicate that child labor is primarily driven by economic hardship, with children engaging in various jobs such as street vending, entertainment, and market labor to support their families. Despite legal protections, many children face difficulties in accessing education due to their work commitments. The study highlights the urgent need for government intervention, emphasizing policies that balance economic support for families while ensuring children's right to education. The implications of this research suggest a more comprehensive social protection strategy and increased public awareness to address child labor effectively.